Implementasi Model Pembelajaran Berbasis Masalah Pada Mata Pelajaran PAI DI SMP 01 Sungai Aur - Silvia Putri; Charles Charles; Wedra Aprison; Endri Yenti (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2023)
This research is motivated by a number of problems, namely the implementation of problem-based learning models in PAI subjects at SMP N 01 Sungai Aur has not been maximally implemented, because it is constrained by the time spent in the teaching and learning process, resulting in some students not understanding the material being taught or requiring reinstatement of the material. The type of research used in this study is using qualitative research. The key informant in this study was the PAI teacher at SMP 01 Sungai Aur, namely Ibuk Asniyan Warti S.Pd. The key informants in this study were students of SMP 01 Sungai Aur who took part in the lesson. The data collection technique is by using documentation, observation, and interviews. The drawback of this model is that it takes a long time for children to get used to it. This PBL model uses many complex techniques for children to understand.